Experiences And Perceptions Of MSME Entrepreneurs In Using E-Commerce Services As A Sales Platform In Indonesia: A Qualitative Approach To The Culinary Sector - Moch. Wahyu Widodo; Rieska Maharani; Rina Maretasari; Agus Hermawan; Ludi Wishnu Wardana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the experiences and perceptions of Micro, Small and Medium Enterprises (MSME) entrepreneurs in using e-commerce services as a sales platform in Indonesia, with a special focus on the culinary sector. Using a qualitative approach, this research involved in-depth interviews with a number of MSME culinary entrepreneurs to collect data regarding motivations, challenges, benefits and impacts of using e-commerce on their businesses. The research results show that e-commerce provides significant opportunities for culinary MSMEs to expand markets and increase sales. However, entrepreneurs also face various obstacles such as lack of technological knowledge, difficulties in logistics, and intense competition. This study concludes that although there are challenges that must be faced, the use of e-commerce can be an effective tool for developing MSME businesses in the culinary sector, provided there is adequate support in terms of education and technological infrastructure. These findings provide important insights for stakeholders in designing policies and programs that support the adoption of e-commerce by MSMEs in Indonesia.